Perinatal behavioral patterns during and after human-animal interactions in rangeland breeding ewes - Schiller, Kaleiah; Horback, Kristina (Frontiers in Animal Science, 2024)
Previous research indicates that traits observed among breeding ewes in restrained contexts during human-animal interactions (HAIs) may have a greater association with maternal care and lamb outcome compared to responses in an open testing environment. The current study investigated the relationship among various behaviors in multiparous ewes (n = 42) in two distinct contexts: 1.) human-animal interactions, with no lamb present, during post-breeding, gestation and weaning in restrained and unrestrained tests and 2.) human-animal interaction, with the lamb present, after parturition. Tests without the lamb present included a Human Contact, Presence and Approach test and tests with the lamb present included a Lamb Handling and Tie Down test. Sheep that groomed the lamb more changed head posture in the Human Contact test frequently (gestation Y2 and weaning Y1 ) and avoided the human ('peripheral zone') in the Human Presence test (gestation Y1 & Y2 and weaning Y1 & Y2 ) (P=0.01). Sheep that assumed a head down posture in the Human Contact test (weaning Y1 & gestation Y2 ) tended to be less environmentally vigilant in the Lamb Tie down test (P<0.10). Proportion of time in the 'peripheral zone' in the Human Presence test, at post-breeding, was a significant, negative predictor of 'environmental vigilance' in the Lamb Tie Down test (P=0.02). The model with 'peripheral zone' as a predictor explained more variance compared to the null (R 2 adjusted= 14.2 vs 8%), however, carried less cumulative model weight compared to the null model (69 vs 31%). A post hoc, negative relationship was found between 'environmental vigilance' and 'sniffing/grooming' the lamb in the Lamb Tie Down test that may have been the basis for other relationships outside of the lambing season. Weaning weights were highly repeatable within ewes (R=0.70, P=0.001, CI[0.29, 0.91] and weaning weight models were improved with inclusion of time in the 'peripheral zone' in the Human Presence test, grooming and 'environmental vigilance' in the Lamb Tie Down test.Behavior outside of the lambing season, during human animal interactions, may be useful in gauging maternal behavior (grooming) and lamb birth and weaning weights.